ANALYSIS OF INDEPENDENT LEARNING AND LITERACY THROUGH AI ON THE QUALITY OF EDUCATION - Dewi, Erni Ratna (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to analyze the influence of independent learning and literacy through artificial intelligence on the quality of education. This type of research uses a quantitative descriptive approach with a sample based on purposive sampling of 236 State Middle School teachers from the Tamalanrea District area. Data collection techniques in this research were through questionnaires, literature study and observation. The data analysis technique uses Structural Equation Modeling (SEM) WarpPLS 7.0 software. The results of data analysis show that the independent learning and literacy variables have a significant effect on artificial intelligence. The variables independent of learning, literacy and artificial intelligence have a significant effect on the quality of education. The independent learning and literacy variables have a significant indirect effect through artificial intelligence on the quality of education